QUALITY PERCEPTION ANALYSIS ON PURCHASE INTENTION (DING TEA BRAND IN BATAM) - Tiurniari Purba; Nora Pitri Nainggolan; Heryenzus Heryenzus (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
Perceived quality can be a company marketing strategy over a product and forming a relationship between producers and consumers. This study aims to examine and analyze the influence of factor effecting purchase intention of brand Ding Tea in Batam. By using purposive sampling obtained 195 respondents. Using multiple linear regression to data analysis and validity, reliability and classical assumption tests. this study proves perceived quality affect purchase intentions. From this study, it is expected that companies pay more attention to product quality and consumer reviews to increase purchase intention.